Entre paisagens e inventários: o projeto literário de Carola Saavedra - Ferreira, Josye Gonçalves (2021)
This research is dedicated to think about the contemporary literature from the study of fiction by Carola Saavedra. Given the idea of a literary project perceived by the writer's work, this doctoral thesis goes through her fictional production, seeking to identify the central elements that act in the composition of a narrative identity as the same time as trying to position it in the contemporary outlook. It appears that the saavedrian project is aligned with those aesthetic movements in which the boundaries of literature are re-dimensioned, expanding on the direction of other artistic fields and destabilizing the fiction’s rules. According to that point of view, this work focuses on the analysis of the novels: The inventory of absent things (2014) and Landscape with Dromedary (2010), books that seem to concentrate some of the main characteristics observed in recent literary production. On the one hand, there is the problematization of some categories such as author, narrator and reader through an act of fictional writing; on the other hand, the dialogue with different codes and the incorporation of procedures from other fields approach the literary discourse of artistic practice. In this sense, the notion of performance emerges, among other theoretical leaders, as a possible key for reading both for the investigation of the narrative process and for the approximation with contemporary art undertaken by the author.